2010
DOI: 10.1371/journal.pntd.0000793
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma vivax Infections: Pushing Ahead with Mouse Models for the Study of Nagana. II. Immunobiological Dysfunctions

Abstract: Trypanosoma vivax is the main species involved in trypanosomosis, but very little is known about the immunobiology of the infective process caused by this parasite. Recently we undertook to further characterize the main parasitological, haematological and pathological characteristics of mouse models of T. vivax infection and noted severe anemia and thrombocytopenia coincident with rising parasitemia. To gain more insight into the organism's immunobiology, we studied lymphocyte populations in central (bone marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 46 publications
5
29
0
Order By: Relevance
“…However, the light emissions we measured clearly demonstrated that growing parasites were accumulating close to the inoculation site. The results we obtained with bioluminescent T. vivax are fully consistent with our previous reports [10] and confirm that the parasite spreads across the spleen and liver compartments. It is interesting to note that lung infiltration by the parasite is difficult or impossible to observe by immunohistopathology, contrasting with our present observations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the light emissions we measured clearly demonstrated that growing parasites were accumulating close to the inoculation site. The results we obtained with bioluminescent T. vivax are fully consistent with our previous reports [10] and confirm that the parasite spreads across the spleen and liver compartments. It is interesting to note that lung infiltration by the parasite is difficult or impossible to observe by immunohistopathology, contrasting with our present observations.…”
Section: Discussionsupporting
confidence: 92%
“…We have previously developed experimental models of T. vivax infection using mice infected with the ILRAD1392 reference strain [9]. Immunobiological and immunophysiopathological analyses confirmed that these models are reliable and consistent with all the relevant characteristics of the animal disease [9], [10]. Furthermore, we have also developed robust methods for parasite growth and differentiation in axenic cultures, paving the way to appropriate conditions for the first genetic manipulation of T. vivax [11].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We used this IL 1392 strain to establish novel mouse models of experimental infection and immunopathology [7], [8]. Today, we report herein on how we managed to overcome the lack of genetic tools for analyzing T. vivax gene expression and function by standardizing the axenic conditions for epimastigote cultivation of the IL 1392 strain and its in vitro differentiation into infectious forms.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have suggested that such genetically identical mice may not serve as an accurate model for the human condition (which are generally outbred) in terms of their immune responses. [10][11][12] To evaluate the utility of the inbred mouse model, outbred mice were also analyzed in these experiments. Both inbred and outbred mice were lethally irradiated and syngeneic BMT (the optimal situation) was performed.…”
Section: Introductionmentioning
confidence: 99%